Risk and criminal victimization. A modernist dilemma? - Walklate, Sandra (The British journal of criminology, 1997)
Over the last 15 years or so the study of criminal victimization has proceeeded apace. That study has frequently drawn together an understanding of the nature and extent of criminal victimization with the question of risk from such victimization. Yet while what is actually meant by criminal victimization has been subject to considerable scrutiny, what is meant by risk in this context has been less closely examined. The purpose of this paper is to suggest that thinking about risk through a gendered lens might better inform those wider concerns of criminal victimization in general